1973
DOI: 10.1128/jb.114.3.934-942.1973
|View full text |Cite
|
Sign up to set email alerts
|

Teichoic Acid of a Stabilized L-Form ofStreptococcus pyogenes

Abstract: A stabilized L-form of Streptococcus pyogenes continues to synthesize glycerol teichoic acid. This polymer was obtained from S. pyogenes and its L-form, treated in identical fashion, and compared. Highly purified glycerol teichoic acid from only the L-form was found to be devoid of D-alanine and to have a shorter chain length. Otherwise, the glycerol teichoic acid from these two organisms was found to be a 1, 3-phosphodiester-linked glycerophosphate polymer substituted with D-glucose. Evidence is presented tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…However, when the peptidoglycan is lost through the action of lysozyme or under the treatment with penicillin and other cell wall inhibitors, LTA is exposed in its full length on the surface of the protoplast or L-form variant. Moreover, L forms of group A streptococci have been found to be no longer able to incorporate alanine into LTA (6), so that the LTA of the L form is lacking alanine ester in contrast to the LTA of bacterial-phase cells (29,34). It is of interest in this context that L variants of S. aureus and S. faecalis have been reported to activate complement via the alternative pathway, which resulted in death of these cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, when the peptidoglycan is lost through the action of lysozyme or under the treatment with penicillin and other cell wall inhibitors, LTA is exposed in its full length on the surface of the protoplast or L-form variant. Moreover, L forms of group A streptococci have been found to be no longer able to incorporate alanine into LTA (6), so that the LTA of the L form is lacking alanine ester in contrast to the LTA of bacterial-phase cells (29,34). It is of interest in this context that L variants of S. aureus and S. faecalis have been reported to activate complement via the alternative pathway, which resulted in death of these cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although it was shown that addition of salt to peptidoglycan synthetase reaction mixtures inhibited the streptococcal enzyme severely at concentrations of salt similar to that employed in the b-form growth medium, it does not follow that this difference between the two growth media is directly responsible for the inability of the L-form to synthesize peptidoglycan because the parent streptococcus synthesizes a cell wall when grown in L-form medium (24). Also, this L-form is still unable to synthesize a rigid cell wall when adapted to grow in physiologically isotonic media (C. Panos and 0.…”
Section: Temperature (C)mentioning
confidence: 99%
“…Therefore, L-form cytotoxicity appears to be equally as effective for cultured mouse glomeruli and human cell monolayers. Bar, 1 1>m. an earlier study that had documented the lack of any apparent difference in the destructive ability of the LTA isolated from either the L-form or its parental S. pyogenes for human kidney monolayers in tissue culture despite differences in the length and composition of this amphiphile from these two organisms (13,14). Finally, and as opposed to an earlier study with cultured human cell monolayers (1), glomerular destruction did not increase when the concentration of LTA was increased.…”
Section: Discussionmentioning
confidence: 61%